PENGARUH MOVING CLASS DAN KREATIVITAS BELAJAR TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN FIKIH DI KELAS VIII MADRASAH TSANAWIYAH DARUSSALAM SIMPANG LIMUN KAB. LABUHANBATU SELATAN - Fairuz, Ahmad; Hidayati; Masyhudi, Fauza; Sepriyanti, Nana; Asril, Zainal (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2025)
Ahmad Fairuz Batubara. 2024. The Influence of Moving Class and Learning Creativity on Student Learning Outcomes in Jurisprudence Subjects in Class VIII Madrasah Tsanawiyah Darussalam Simpang Limun Labuhanbatu Selatan. Thesis. Postgraduate Islamic Religious Education Masters Study Program, Imam Bonjol State Islamic University, Padang. This research is motivated by the gap between theory and practice in the field. It was explained that theory, moving classes and student learning creativity influence student achievement and learning outcomes, however, the reality in the field is that moving classes and student learning creativity have not had an influence on student learning outcomes. This research aims to describe: 1) the influence of moving class on learning outcomes, 2) the influence of learning creativity on learning outcomes, 3) the influence of moving class and learning creativity together on student learning outcomes. This research uses a quantitative descriptive correlational type method.The respondents in this research were class VIII students at MTs Darussalam Simpang Limun. The research sample was taken as a whole from the existing population of 81 people. The research instrument uses a questionnaire with a Likert scale model. Data were analyzed using descriptive statistics, simple regression and multiple regression. The research findings show that: (1) There is a positive and significant influence between moving class on learning outcomes with an achievement of 30.6%, (2) There is a positive and significant influence between learning creativity on learning outcomes with an achievement of 18.5%, (3) ) There is a positive and significant influence between moving classes and learning creativity on student learning outcomes with an achievement of 30.5%. Based on this explanation, it can be interpreted that the high and low learning outcomes of students are determined by the high and low levels of each moving class variable and learning creativity. Therefore, to improve learning outcomes, moving classes and high learning creativity are needed. Recommendations in the research refer to other variables that have an influence on student learning outcomes. This research only describes the influence of moving class variables and learning creativity on student learning outcomes at MTs Darussalam Simpang Limun, Torgamba District, South Labuhanbatu Regency